Characterizing Low-Energy Charged Particles in the Magnetosphere with the LEM CubeSat Spectrometer Project: Detector Concept and Hardware Characterisation - Riccardo Nicolaidis; Francesco Nozzoli; Giancarlo Pepponi; Pierluigi Bellutti; Evgeny Demenev; Francesco Maria Follega; Roberto Iuppa; Veronica Vilona (Universe, 2023)
An accurate flux measurement of low-energy charged particles trapped in the magnetosphere is necessary for space weather characterization and to study the coupling between the lithosphere and magnetosphere, which allows for the investigation of the correlations between seismic events and particle precipitation from Van Allen belts. In this work, the project of a CubeSat space spectrometer, the low-energy module (LEM), is shown. The detector will be able to perform an event-based measurement of the energy, arrival direction, and composition of low-energy charged particles down to 0.1 MeV. Moreover, thanks to a CdZnTe mini-calorimeter, the LEM spectrometer also allows for photon detection in the sub-MeV range, joining the quest for the investigation of the nature of gamma-ray bursts (GRBs) and terrestrial gamma-ray flashes (TGFs). The particle identification of the LEM relies on the <semantics>ΔE−E</semantics> technique performed by thin silicon detectors. This multipurpose spectrometer will fit within a 10 × 10 × 10 <semantics>cm3</semantics> CubeSat frame, and it will be constructed as a joint project between the University of Trento, FBK, and INFN-TIFPA. To fulfil the size and mass requirements, an innovative approach, based on active particle collimation, was designed for the LEM; this avoids the heavy/bulky passive collimators of previous space detectors. In this paper, we will present the LEM geometry, its detection concept, the results from the developed GEANT4 simulation, and some characterisations of a candidate silicon detector for the instrument payload.